Entre a cela e a sala de aula: um estudo sobre experiências educacionais de educadores presos no sistema prisional paulista - Carvalho, Odair França de (2014)
This study has as its object of study the experience of inmates who are monitors/educators in the education of adult prisoners in the São Paulo penitentiary system. The research field was constituted by six prisons: Penitenciária de Serra Azul I, Penitenciária de Serra Azul II, Penitenciária Desembargador Adriano Marrey Guarulhos I, Penitenciária José Parada Neto Guarulhos II, Penitenciária Feminina do Butantã CPP and Penitenciária Dr. Sebastiao Martins Siqueira. There were 30 subjects, 28 men and 02 women, 27 being prisoners monitors and 03 educational managers. The specific objectives were: a) revisiting historical dimensions of the prison institution and its constitution, as well as characterize the Brazilian prison system, deepening particularities of the constituent aspects in São Paulo and in the prisons investigated; b) analyzing the legal and curricular guidelines of the education in prison; c) recording and reflecting on the identity of the educators who are prisoners; d) registering, reflecting and analyzing the concepts, knowledge and practices of educators who are prisoners in what relates to citizenship, education, justice in the context of the Department of Penitentiary Administration of São Paulo state. It was a qualitative research based on the procedures of oral history in an interdisciplinary vision. In order to achieve the objectives the following instruments were chosen: literature search; analysis of written documents such as laws, guidelines, educational material; and conducting oral interviews with inmates who are educators and managers. We also used theoretical contributions of cultural studies, narrative research, teachers education, teacher knowledge and the education of young and adult people (EYAP). The narratives of prisoners who are educators revealed a different profile, since they come from well-structured families, work inside and outside the prison and keep good family relationship. Four of the monitors have a college degree and the others have graduated in high school. Another identified trait among them was that of religious conversion in prison. Some of them have become educators and religious leaders. A number of reasons have motivated them to become educators in prison. Inmates monitors were considered good teachers, even without proper training. With the difficulties they admitted that they could develop a better work with the input of other learning materials. The analysis of the educational proposal and the voices of the subjects evidenced that the experience conducted by FUNAP was successful since it valued the subjects and the construction of knowledge and unique practices in the prison educational environment. That way it deserves to be preserved and valued. We have concluded that education in prison should not be a mere transposition of the process developed in regular schools, but a specific EYAP that considers the singularities of the prison environment and subjects as teachers to acknowledge the contradictions, and values the freirean ideals of liberating and emancipator education.